(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this article, we propose a reflection on the agendas linked to female alterities, taking the body as our starting point. To embody our discussions, we have chosen performances by three Brazilian artists as our object of analysis in order to develop concepts such as the corpo esgotado (Lapoujade), but above all to think of the body in an aesthetic perspective, as a support, expression and artistic language, in which movements of grievance and uprising can be enunciated.